User Involvement of People with Mild Disabilities in Technology Innovations: Does It Make a Difference? - Borch, Anita (Social Inclusion, 2019)
In this study, we explored the role of people with mild forms of visual, hearing, physical, and cognitive impairments in innovation processes. Our research questions are: do the product evaluations by people with mild disabilities differ from those given by people without reported disabilities? If so, how? The analysis is based on eight focus group interviews conducted in Norway in 2016, in which 60 participants were asked to evaluate 11 energy-efficient product ideas. Four of the focus groups (two of men and two of women) were recruited based on the criteria of being mildly disabled. The remaining groups (two of men and two of women) had no such clause. The research results are ambiguous, indicating that the evaluations of new innovation by mildly disabled people correspond with those made by people without reported disabilities in some aspects and differ in others. However, the small size of the sample studied in this article suggests that the research results must be regarded as preliminary. Overall, the study reveals some interesting observations to be confirmed and disconfirmed in further research.